Factors Influencing Teacher Performance and Work Motivation in a Middle School Environment in Central Jakarta - Harsono Harsono; Hapzi Ali; Achmad Fauzi (DINASTI RESEARCH, 2023)
In this study using a quantitative approach with a population and a sample of 80 samples, the object studied in this study was a public junior high school teacher in central Jakarta, the analytical tool used was PLS Version 3.0 and the results obtained were, Style Leadership has a Significant Influence on teacher performance, the School Environment has a Significant Influence on teacher performance, Motivation has a Significant Influence on teacher performance.